2016
DOI: 10.1053/j.jvca.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Extracorporeal Membrane Oxygenation Teams: The North American Versus the European Experience

Abstract: Objective To evaluate differences in the inclusion of anesthesiologists in mobile extracorporeal membrane oxygenation (ECMO) teams between North American and European centers. Design A retrospective review of North American versus European mobile ECMO teams. The search terms used to identify relevant articles were the following: “extracorporeal membrane transport,” “mobile ECMO,” and “interhospital transport.” Setting MEDLINE review of articles. Participants None. Interventions None. Results Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In each of these descriptions, patient selection, stringent adherence to safety protocols, and significant investment in personnel education and training represent the sine qua non of inter-facility ECMO transport. Although the specific makeup of the ECMO transport team appears to have some geographical variation, with European centers incorporating more anesthesiologists relative to North American centers, 87 the consistent elements in all ECMO transport centers lie in exhaustive preparation and both individual and team education and training.…”
Section: Ecmo Transportmentioning
confidence: 99%
“…In each of these descriptions, patient selection, stringent adherence to safety protocols, and significant investment in personnel education and training represent the sine qua non of inter-facility ECMO transport. Although the specific makeup of the ECMO transport team appears to have some geographical variation, with European centers incorporating more anesthesiologists relative to North American centers, 87 the consistent elements in all ECMO transport centers lie in exhaustive preparation and both individual and team education and training.…”
Section: Ecmo Transportmentioning
confidence: 99%
“…14,15 A recent review of transports on ECMO in North America and Europe by Nwozuzu and colleagues established that North American transports are much less likely to have an anesthesiologist on board compared to European transports and suggested that there should be more accompanied transports. 22 These recommendations appeared based on qualitative observations of adverse events in ECMO transports and an experienced respect for the challenge of responding to complications that may occur in patients on ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Extracorporeal Life Support Organization (ELSO, Ann Arbor, MI, USA; www.elso.org) published guidelines for ECMO transport team implementation. 17 Nwozuzu et al 18 demonstrated the significant discrepancies in the inclusion of anesthesiologist/intensivist on mobile ECMO teams, with European centers more likely to incorporate them into the team. To our point of view, inclusion of a specialized anesthesiologist/intensivist into the pediatric mobile ECMO team is absolutely essential.…”
Section: Discussionmentioning
confidence: 99%